The Relationship between Emotional Intelligence and Self-Confidence of Group B Children at Al Anshor Islamic Kindergarten - Della, Shinta; Rukiyah, Rukiyah (Universitas Pahlawan Tuanku Tambusai, 2025)
Early Childhood Education (ECE) aims to support the holistic growth and development of children, encompassing six key aspects: religious values, physical development, language skills, cognitive abilities, artistic expression, and social-emotional well-being. Among these, self-confidence is a vital component of emotional intelligence that must be nurtured through appropriate strategies, such as role-playing. Support from both parents and teachers plays a crucial role in shaping children’s self-confidence. This study aims to examine the relationship between emotional intelligence and self-confidence in Group B children at Al-Anshor Islamic Kindergarten, located in Talang Kelapa District, Banyuasin Regency. The research employed a quantitative correlational design, with data collected using a structured (closed-ended) questionnaire. The results revealed a very strong relationship between emotional intelligence and self-confidence among the children. This was confirmed through a hypothesis test using the Pearson Product Moment correlation, which yielded a calculated r value of 0.904, exceeding the r table value of 0.468 at a 5% significance level (df = 19 - 2). Therefore, the alternative hypothesis (Ha) is accepted, indicating that higher emotional intelligence is associated with higher levels of self-confidence in children. Furthermore, the study found that the majority of children fell into the moderate category for both emotional intelligence and self-confidence, with 63.2% of participants exhibiting moderate levels in each area. These findings can serve as a valuable reference for educators and parents to design effective interventions and strategies aimed at enhancing emotional intelligence and self-confidence in children aged 5–6 years.